Recent history of Brazilian Sign Language and Portuguese translation and interpreting at the Universidade Federal do Espírito Santo (2006–2021) (PERcursos Linguísticos, 2022)
This article documents the history of translation and interpreting of Brazilian Sign Language (Libras) and Portuguese at the Universidade Federal do Espírito Santo (Ufes). To this end, it is based on the Sign Languages Translation and Interpreting Studies, as well as in the field of History of Translation and Translation and Interpreting Policies to analyze a set of documents temporally comprised between the years 2006 and 2021 such as contracting notices and appointments in the Diário Oficial da União, in addition to institutional ordinances, regulations and reports. In the first two decades of the 21st century, at least three movements can be observed that mark the recent history of these activities at the institution: (i) the interpreting emergence financed by scholarships granted to students; (ii) the professional formalization of translation and interpreting through the hiring of civil servants through a public tender; and (iii) the grouping of professional translators and interpreters into a single sector. These movements mark the development of a translation and interpreting policy in the institutional domain of Ufes and the study of them makes it possible to highlight the challenges and advances in sign language translation and interpreting practices in public service contexts.
Keywords: Translation and interpreting; Brazilian Sign Language and Portuguese; History of translation; Translation and interpreting policies; Translation and interpreting of public services